Niche Differentiation of Comammox Nitrospira in the Mudflat and Reclaimed Agricultural Soils Along the North Branch of Yangtze River Estuary - Wang, Xinxin; Lu, Lu; Zhou, Xue; Tang, Xiufeng; Kuang, Lu; Chen, Junhui; Shan, Jun; Lu, Huijie; Qin, Hua; Adams, Jonathan; Wang, Baozhan (Frontiers in Microbiology, 2021)
The discovery of complete ammonia oxidation (comammox), oxidizing ammonia to nitrate via nitrite in a single organism, has redefined the traditional recognition of the two-step nitrification driven by two functional groups (ammonia-oxidizing and nitrite-oxidizing microorganisms). However, the understanding of the distribution and niche differentiation of comammox Nitrospira in the estuarine mudflats and their reclaimed agricultural soils is still limited. Here, we investigated the abundance, diversity and community structures of comammox Nitrospira in the mudflats and the reclaimed agricultural soils in the northern Yangtze River estuary. Quantitative PCR showed the abundances of amoA genes of comammox were lower than that of ammonia-oxidizing bacteria (AOB) in nearly all samples. Amplicon sequencing of amoA genes revealed that the community structures of comammox Nitrospira were significantly (P < 0.001) different between the original mudflats and the reclaimed agricultural soils, indicating niche differentiation among comammox Nitrospira clades (clade A.1, clade A.2 and clade B). The clade A.1 was the dominant group of comammox Nitrospira in the mudflats, while clade B predominated in the agricultural soils. However, the members of clade A.2 could be clearly divided into two groups, the mudflat-preferred and agricultural soil-preferred groups, suggesting more complicated ecological preferences within this sub-clade. Furthermore, it was demonstrated that salinity, organic matter (OM) and NO3--N had a significantly influence on the distribution of comammox Nitrospira in the estuarine environment. Clade A.1 and nearly half members of clade A.2 were positively correlated with salinity, and negatively correlated with the concentrations of OM and NO3--N. In contrast, the clade B and the other half members of clade A.2 showed the exact opposite pattern: a negative correlation with salinity and positive correlation with OM and NO3--N. The co-occurrence network demonstrated that the operational taxonomic units (OTUs) within the same (sub-)clade were mostly positively correlated, indicating the similar niche preferences among the members from the same (sub-)clade of comammox Nitrospira. Taken together, our results revealed the niche differentiation of comammox Nitrospira in estuarine ecosystems where salinity and OM were the primary factor responsible for the distinct ecological distribution patterns.